Community prevalence, mechanisms and outcome of mitral or tricuspid regurgitation. Issue 12 (4th March 2021) - Cahill, Thomas J; Prothero, Anthony; Wilson, Jo; Kennedy, Andrew; Brubert, Jacob; Masters, Megan; Newton, James D; Dawkins, Sam; Enriquez-Sarano, Maurice; Prendergast, Bernard D; Myerson, Saul G
Abstract : Objective: The study aims were (1) to identify the community prevalence of moderate or greater mitral or tricuspid regurgitation (MR/TR), (2) to compare subjects identified by population screening with those with known valvular heart disease (VHD), (3) to understand the mechanisms of MR/TR and (4) to assess the rate of valve intervention and long-term outcome. Methods: Adults aged ≥65 years registered at seven family medicine practices in Oxfordshire, UK were screened for inclusion (n=9504). Subjects with known VHD were identified from hospital records and those without VHD invited to undergo transthoracic echocardiography (TTE) within the Oxford Valvular Heart Disease Population Study (OxVALVE). The study population ultimately comprised 4755 subjects. The severity and aetiology of MR and TR were assessed by integrated comprehensive TTE assessment. Results: The prevalence of moderate or greater MR and TR was 3.5% (95% CI 3.1 to 3.8) and 2.6% (95% CI 2.3 to 2.9), respectively. Primary MR was the most common aetiology (124/203, 61.1%). Almost half of cases were newly diagnosed by screening: MR 98/203 (48.3%), TR 69/155 (44.5%). Subjects diagnosed by screening were less symptomatic, more likely to have primary MR and had a lower incidence of aortic valve disease. Surgical intervention was undertaken in six subjects (2.4%) over a median follow-up of 64 months. Five-year survival was 79.8% in subjects with isolated MR, 84.8% in those with isolated TR, and 59.4% in those with combined MR and TR (p=0.0005). Conclusions: Moderate or greater MR/TR is common, age-dependent and is underdiagnosed. Current rates of valve intervention are extremely low.